Plasma-assisted atomic layer deposition of TiO2 compact layers for flexible mesostructured perovskite solar cells. (1st July 2017) - Zardetto, V.; Di Giacomo, F.; Lucarelli, G.; Kessels, W.M.M.; Brown, T.M.; Creatore, M.
Graphical abstract: Highlights: Low temperature atomic layer deposition (ALD) for TiO2 layer on ITO-PET substrates. 5 nm thick ALD TiO2 film enables efficient flexible mesostructured perovskite device. A maximum of 9.2% efficient flexible perovskite device has been achieved. ALD provides higher performance with respect to the solution processed technique. Excellent hole blocking behaviour of the ALD TiO2 layer. Abstract: In mesostructured perovskite solar cell devices, charge recombination processes at the interface between the transparent conductive oxide, perovskite and hole transport layer are suppressed by depositing an efficient compact TiO2 blocking layer. In this contribution we investigate the role of the atomic layer deposited TiO2 on ITO-PET substrates in hybrid halide (CH3 NH3 PbI3−x Clx ) perovskite solar cells. In the absence of the TiO2 layer, very low open circuit voltage (VOC = 35 mV) and efficiency (η = 0.02%) values are observed. The analysis of JV dark current reveals the lack of rectifying behaviour at the above-mentioned interface. The introduction of ultra-thin ALD layers (from 2.5 to 44 nm) leads to an increment in all the photovoltaic parameters and, consequently, in the photovoltaic conversion efficiency. A maximum power conversion efficiency of 9.2% is achieved, much higher than the 4% obtained when a low temperature conventional sol gel TiO2 compact layer is used. The higher quality of the ALD layer in terms of low defect density and low level of impurities with respect to the solution processed approach has been highlighted by electrochemical characterization and XPS analysis.